Multiple utility constrained multi-objective programs using Bayesian theory - Pooneh Abbasian; Nezam Mahdavi-Amiri; Hamed Fazlollahtabar (Journal of Industrial Engineering International, 2018)
A utility function is an important tool for representing a DM's preference. We adjoin utility functions to multi-objective optimization problems. In current studies, usually one utility function is used for each objective function. Situations may arise for a goal to have multiple utility functions. Here, we consider a constrained multi-objective problem with each objective having multiple utility functions. We induce the probability of the utilities for each objective function using Bayesian theory. Illustrative examples considering dependence and independence of variables are worked through to demonstrate the usefulness of the proposed model.
Keywords: 650; Multi-objective program; Utility function; Bayesian theory